2012
DOI: 10.1007/s00397-012-0620-3
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the laminar oscillatory flow of wormlike micellar solutions

Abstract: We report new experimental results of the oscillatory flow of a solution of giant micelles in a narrow vertical tube. We explore small driving amplitudes (laminar flow) and a large range of driving frequencies. High-resolution particle image velocimetry measurements of the flow field in a meridional plane of the tube show that the velocity magnitude at the tube axis peaks at well-defined resonance frequencies, where the phase lag with the forcing changes abruptly. The velocity field is highly inflectional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…For water, the recirculation induced by the presence of the top and bottom endwalls seems not to have influence on the flow in the middle of the cylinder for aspect ratios above 20 [26]. In experiments with viscoelastic WLM solutions in a cylinder of 560 mm length and 50 mm diameter the recirculating flow at the top and bottom lids did not extend beyond 20 mm [27]. Suppose that the top and bottom lids oscillate in time according to z(t) = z 0 sin (ω 0 t).…”
Section: (B) Fluid Motion In a Vertical Cylindermentioning
confidence: 89%
See 2 more Smart Citations
“…For water, the recirculation induced by the presence of the top and bottom endwalls seems not to have influence on the flow in the middle of the cylinder for aspect ratios above 20 [26]. In experiments with viscoelastic WLM solutions in a cylinder of 560 mm length and 50 mm diameter the recirculating flow at the top and bottom lids did not extend beyond 20 mm [27]. Suppose that the top and bottom lids oscillate in time according to z(t) = z 0 sin (ω 0 t).…”
Section: (B) Fluid Motion In a Vertical Cylindermentioning
confidence: 89%
“…indeed the highly reversing nature of the base flow and the presence of resonant frequencies [27,34,35]. In particular, figure 3 shows the experimental results obtained at the symmetry axis of the cylinder.…”
Section: (C) Flow Resonancesmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of Andrienko et al [226] obtained in the very late 1990s were confirmed by the recent experimental and analytical research of Casanellas and Ortín [231,232] who reported analytical studies of the laminar oscillatory flow of Maxwell and Oldroyd-B type of viscoelastic fluids in rectangular and cylindrical cross-sectional tubes and experimental results of the oscillatory flow of a solution of giant micelles in a narrow vertical tube under small driving amplitudes in laminar flow and a large range of driving frequencies. Their theoretical analysis shows that there are resonant velocity peaks under certain conditions and that a very small additive Newtonian solvent contribution is sufficient to largely suppress the resonant behavior thereby confirming the conclusions of Andrienko et al [216].…”
Section: Fig 51mentioning
confidence: 60%
“…2003). Some significant deviations in the Maxwell behaviour are observed for intermediate- and high-frequency regimes for wormlike micellar solutions due to the Rouse-like behaviour of the individual entangled segments (Yesilata, Clasen & Mckinley 2006) and additional solvent stress (Casanellas & Ortín 2012).…”
Section: Introductionmentioning
confidence: 99%